METABOLIC ENGINEERING OF MICROORGANISM FOR THE PRODUCTION OF CARBOXYLIC ACID AND THEIR INHIBITORY EFFECTS. - SARFRAZ, HIRA; ALI, SIKANDER; MUSHTAQ, JAVERIA; NAZIR, FARZANA (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
To fulfill the requirement of futurre coming perspective for chemicals like carboxylic acid thatare produced by microbial fermentation are an excellent biorenewable chemical. Due to theirdemand and usage as precursor for a number of industrial chemical, it can be produced throughengineered microbes such as Saccharomyces cerevisiae, E.coli and Bascilus subtilis. Geneticengineering is now successfully and commonly used to change carbon to ethanol the endproduct of Saccharomyces cerevisiae to pyruvate. Genetic manipulation methods are useful forpathway design and for the production of several organic acids. Deletions of metabolicpathways that compete with the target compound are produces, can be a useful method forredirecting metabolic flux into the desired pathways. However carboxylic acids becomeincreasingly inhibiting to the microorganisms. These inhibitors at their specific potency arecommonly used as food preservative. The effects of carboxylic acids include cell membranedamage, change in microbial internal pH. Certain changes in cell membrane properties such asfluidity, composition, integrity and intracellular pH and hydrophobicity are associated withincrease tolerance. These desirable products can use in the engineering of robust strains withimproved industrial performance.